LARANGAN MENYAKITI SESAMA DALAM HADIS NABI SEBAGAI DASAR PENCEGAHAN BULLIYING DI PESANTREN - Makrunatul Hasanah (Adisam Publisher, 2025)
The phenomenon of bullying in educational institutions, including Islamic boarding schools, is a serious problem that can hinder the educational process, reduce academic achievement, and cause long-term psychological effects on victims. As institutions founded on Islamic values, Islamic boarding schools need a strong normative foundation to build a safe, ethical, and civilised educational culture. This study examines the hadiths of the Prophet Muhammad, which explicitly and implicitly emphasise the prohibition of harming others, whether through physical, verbal, or psychological actions. This prohibition is positioned as a theological foundation for the development of strategies to prevent bullying in Islamic boarding schools. Through an in-depth study of relevant hadiths, such as the prohibition of harming one another (lā taḍārrū), the prohibition of insulting, the prohibition of belittling, and the command to guard one's tongue, this study shows that prophetic values substantially support efforts to create a safe and humane pesantren environment. The results of this study are expected to contribute conceptually to the development of character building programmes, a hadith-based anti-bullying curriculum, and the strengthening of the role of caregivers and senior students in building a culture of mutual respect.